Convex hull based trajectory design for mobile sink in wireless sensor networks. (2019) - Nitesh, Kumar; Jana, Prasanta K.
Data collection through mobile sink (MS) is an efficient solution to solve hotspot or sinkhole problem which is usually caused by data collection using a static sink. In this paper, we propose an algorithm for designing a delay bound path for MS which is based on convex hull and therefore we refer it a concentric convex hull (CCH) algorithm. For a given set of sensor nodes, the CCH generates a set of convex hull as the potential paths and selects one of them as the final path for MS fulfilling certain optimising criteria. Unlike other existing techniques, the proposed technique does not use travelling sales person (TSP) tour. This, in turn, reduces the hop count and restricts the time complexity of the proposed technique to O(n2) for n sensor nodes. We simulate the proposed algorithm, compare and analyse the results with some of the existing algorithms over diverse network performance metrics.